Concentration of sheep manure bacteria in the immobilization of arsenic from groundwater using zero-valent - Wahyu Wilopo; Keiko Sasaki; Tsuyoshi Hirajim (Geological Engineering Department Universitas Gadjah Mada, 2015)
Permeable reactive barrier column tests were performed to investigate whether anaerobic bacteria in sheep manure could help remove As from groundwater. One column served as a control and was packed with zero-valent iron (ZVI), compost leaf, wood chips, glass beads, and gravel, after which it was sterilized. The other (‘inoculated column’) was packed with the same ingredients, with the addition of sheep manure as a source of anaerobic bacteria. Simulated As-contaminated groundwater was prepared based on groundwater samples from Sumbawa Island, Indonesia, but with the arsenic concentration adjusted to 50 mg/L. The inoculated column was found to remove As more effectively from the simulated groundwater than the sterilized one. A gradual decrease in sulfate concentration was observed in the inoculated column at the rate of 0.26 mmol of sulfate/L/day, suggesting that there was sulfate-reducing activity in the microbial population. In addition, the sulfur isotope ratio showed -4.3 (‰) and 0.2 (‰) in influent and effluent, respectively, indicating that sulfate-reducing bacteria (SRB) consumed δ32S preferentially. Using population size estimates from the most probable number (MPN) method, the population of SRB was found to increase with distance traveled in the column. Profiling the community composition of the bacteria in different fractions of the inoculated column using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) on 16S rRNA sequences suggested that a majority of bacteria were various Clostridium species and one species of Proteobacteria, Geobacter metallireducens GS-15. Some of them may contribute to the removal of arsenic.Keywords: Sheep manure, zero valence iron, arsenic, immobilization, sulfate-reducing bacteria